Xrcc5/KU80 is not required for the survival or activation of prophase-arrested oocytes in primordial follicles - Ratnayaka-Gamage, Natasha D.; Alesi, Lauren R.; Zerafa, Nadeen; Stringer, Jessica M.; Hutt, Karla J. (Frontiers in Endocrinology, 2023)
The non-growing, meiotically-arrested oocytes housed within primordial follicles are exquisitely sensitive to genotoxic insults from endogenous and exogenous sources. Even a single DNA double-strand break (DSB) can trigger oocyte apoptosis, which can lead to accelerated depletion of the ovarian reserve, early loss of fertility and menopause. Therefore, repair of DNA damage is important for preserving the quality oocytes to sustain fertility across the reproductive lifespan. This study aimed to evaluate the role of KU80 (encoded by the XRCC5 gene) – an essential component of the non-homologous end joining (NHEJ) pathway – in the repair of oocyte DNA DSBs during reproductive ageing, and following insult caused by the DNA-damaging chemotherapies cyclophosphamide and cisplatin. The number of healthy follicles, atretic (dying) follicles, and corpora lutea were similar in ovaries from mice with a conditional deletion of Xrcc5 in oocytes (Xrcc5 cKO) and wildtype littermate controls (WT) at PN50, PN200 and PN300. Additionally, primordial follicle number and ovulation rates were similar in young adult WT and Xrcc5 cKO mice following treatment with cyclophosphamide (75mg/kg), cisplatin (4mg/kg), or vehicle control (saline). These data indicate that KU80 is not required for maintenance of the ovarian reserve, follicle development, or ovulation during maternal ageing. Furthermore, KU80 was not essential for the repair of exogenously induced DNA damage in primordial follicle oocytes. The findings of this study indicate that KU80 is not required for the repair of DSBs in the prophase-arrested oocytes of primordial follicles.